Contribution of English Speech Competition on Students’ Motivation and Self-Confidence For Public Speaking at SMA Negeri 1 Gebang - Suparjo; Erika Sinambela; Lastri Wahyuni x Manurung (Merwin Publisher, 2025)
This research aims to determine the contribution of English speech competitions on students’ motivation and self-confidence levels at SMAN 1 GEBANG. Through a descriptive qualitative approach, this research explores a deep understanding of students' experiences participating in speech competitions and their contribution to motivation and confidence. Data collection was carried out with a systematic procedure through filling out questionnaires and interviews with 12 students who participated in the competition from 747 students in classes X, XI, and XII. There were 37.9% strongly agreed, 38.3% agreed, 21.9% disagreed and 3.1% strongly disagreed, stating that English speech competitions contributed positively to students’ motivation, and There were 9 out of 12 respondents delivered that English speech competitions contributed positively to trust in public speaking. The researcher concluded that English speech competitions contribute positively to their motivation and confidence. These findings highlight the importance of competition activities as a means to develop speaking skills and boost students' confidence in the context of English communication. The implications of this research provide a deep understanding of the benefits of English speech competitions in helping students explore their potential in terms of motivation and confidence in public speaking.